Towards more sustainable building based on modified Portland cements through partial substitution by engineered feldspars. (1st February 2021) - Enríquez, E.; Torres-Carrasco, M.; Cabrera, M.J.; Muñoz, D.; Fernández, J.F.
Abstract: Global warming is one of the main problems that facing modern civilization. As buildings consume 40% of total energy, the heating in the cities is a primary concern. Therefore, it seeks to improve sustainable construction materials with better thermal and reflective properties, reducing consumption and heat islands. In this work, mineral and engineered feldspars have been used as partial substitution of white cement, that is widely used in the cladding of façades mainly due to its high whiteness, to improve composites' reflectance and reducing their thermal conductivity. Both feldspars show pozzolanic effect and new composites have superior whiteness and reflectance (greater than12%). Moreover, the engineered feldspar avoids the alkali-silica reaction (ASR) effect in spite of its alkaline content. A reduction of heat of greater than 2 °C after 6 h of solar irradiance is demonstrated for engineered feldspar composite resulting in a good alternative for their implementation as exterior insulation and finish systems.